PROVERBS AND PROVERBIAL THINKING WITHIN LOUISE BENNETT’S POETRY - Lobban, Aileen (Proverbium - Yearbook, 2025)
This article examines the poetry of Louise Bennett (1919 – 2006) using the concept of proverbial thinking to explore the impact of the proverbs in her poems. Proverbial thinking is used as a broad term referring to diverse methods of using, collecting, and preserving proverbs, which in turn activates a sense of urgency surrounding the need to preserve and protect a body of knowledge. Looking at proverbial thinking is also about pointing out elements of proverbial use and knowledge that are not always obvious and that become even more interesting when analysed. Bennett’s own collection of proverbs, here entitled the Proverb Manuscript, serves as a means of expanding the interpretations of the proverbs. The moral and thematic headings under which Bennett places each proverb in the Proverb Manuscript are considered integral to understanding the malleability of the proverb form. The openness of the concept of proverbial thinking also allows for discussion of many of the central topics which surround Bennett, whose career crucially straddles the shifting cultural moment when Jamaica gained independence in 1962. Overall, the article illustrates the multiplicity of proverbial thinking that reflects the layers of complexity within Bennett’s poems, which are written exclusively in Creole.